2020
DOI: 10.1108/mf-04-2019-0154
|View full text |Cite
|
Sign up to set email alerts
|

CEO compensation and firm performance in the insurance industry

Abstract: PurposeWe investigate the relationship between chief executive officer (CEO) compensation and a firm's financial performance in the insurance industry to determine CEO pay policies that are more effective in promoting specific financial corporate goals.Design/methodology/approachConsidering different components of executive pay, we investigate the latter’s relationship with the corporate performance of the insurance industry using the generalized method of moments (GMM) model developed for dynamic panel estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…The findings support the theoretical proposition of agency theory that performance should be used as a positive driver of CEO pay to align the managers' and shareholders' interests (Al‐Shammari, 2021; Amewu & Alagidede, 2021; Dang et al, 2021; Hu & Xu, 2021; Jensen & Meckling, 1976; Ko et al, 2020; Yang et al, 2020; Zoghlami, 2021). This finding equally confirms the research outputs of extant studies such as Chen et al (2021), Bouteska and Mefteh‐Wali (2021), Singh et al (2021), Al‐Faryan (2021), Ibrahim et al (2021), and Bhuyan et al (2020) which affirm the theoretical propositions of the classical agency theory. It, however, contradicts the research outcomes of some other studies such as Olaniyi and Obembe (2015, 2017), Duffhues and Kabir (2008), Aduda (2011), and Faria et al (2014) which supports the theoretical stand of managerial power theory that posits CEO pay to be a factor that aggravates agency problem rather than scaling it down (Bebchuk et al, 2011; Bebchuk & Fried, 2003).…”
Section: Presentation and Discussion Of Empirical Findingssupporting
confidence: 84%
“…The findings support the theoretical proposition of agency theory that performance should be used as a positive driver of CEO pay to align the managers' and shareholders' interests (Al‐Shammari, 2021; Amewu & Alagidede, 2021; Dang et al, 2021; Hu & Xu, 2021; Jensen & Meckling, 1976; Ko et al, 2020; Yang et al, 2020; Zoghlami, 2021). This finding equally confirms the research outputs of extant studies such as Chen et al (2021), Bouteska and Mefteh‐Wali (2021), Singh et al (2021), Al‐Faryan (2021), Ibrahim et al (2021), and Bhuyan et al (2020) which affirm the theoretical propositions of the classical agency theory. It, however, contradicts the research outcomes of some other studies such as Olaniyi and Obembe (2015, 2017), Duffhues and Kabir (2008), Aduda (2011), and Faria et al (2014) which supports the theoretical stand of managerial power theory that posits CEO pay to be a factor that aggravates agency problem rather than scaling it down (Bebchuk et al, 2011; Bebchuk & Fried, 2003).…”
Section: Presentation and Discussion Of Empirical Findingssupporting
confidence: 84%
“…The agency issues arising, due to non-alignment of interest between principal and agent, are mitigated by incurring three types of agency costs: monitoring expenses incurred by the principal; bonding expenditures incurred by the agents; and finally, the residual loss, suffered by the principal which is the reduction in welfare experienced by the principal due to aberrant activities of the agent (Jensen and Meckling, 1976). In this scenario, the shareholders, resort to effective boards and stock-based compensation plans to improve the monitoring of management and reduce the agency cost leading to long-term maximization of shareholder wealth (Bhuyan et al , 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Although, Fahlenbrach and Stulz (2011) find that bank CEOs whose incentives are aligned with the interests of shareholders do not perform any better than those whose incentives are not aligned, Bhuyan, et al (2020) who examined compensation schemes in the insurance industry found that compensation schemes are closely related to the company's financial performance in the future.…”
Section: Truth Inducing Vs Slack Inducing On Budgetary Slackmentioning
confidence: 99%